Research Review: A systematic review and meta‐analysis of infant and toddler temperament as predictors of childhood attention‐deficit/hyperactivity disorder. (4th January 2023) - Joseph, Heather M.; Lorenzo, Nicole E.; Fisher, Nadiyah; Novick, Danielle R.; Gibson, Cassandra; Rothenberger, Scott D.; Foust, Jill E.; Chronis‐Tuscano, Andrea
Abstract : Background: Attention‐deficit/hyperactivity disorder (ADHD) is a common neurodevelopmental disorder with onset as early as preschool and impairment across the lifespan. Temperament factors, specifically those that theoretically map onto ADHD symptoms, may be early markers of risk for developing later childhood ADHD that could be identifiable in infancy or toddlerhood. This meta‐analysis examined the associations between these early temperamental factors and later symptoms and diagnosis of ADHD and mapped early temperament constructs onto the three ADHD symptom dimensions. Methods: A systemic review of the literature was conducted to identify prospective longitudinal studies that included theoretically relevant temperament constructs (sustained attention, activity level, inhibition, and negative emotionality) examined from birth to 36 months old and ADHD (symptoms or diagnosis) in preschool or childhood. The association between each temperament construct and ADHD outcomes was examined using pooled standardized estimates in meta‐analyses. Results: Forty‐eight articles ( n = 112, 716 infants/toddlers) prospectively examined temperament and the relation to childhood ADHD symptoms or diagnosis. Activity level ( k = 18) in infancy and toddlerhood was moderately associated with childhood ADHD ( r = .39, CI = 0.27, 0.51, p < .001). Moderate effect sizes were also observed for sustained attention ( k = 9; r = −.28, CI = −0.42, −0.12, p < .001) and negative emotionality ( k = 33; r = .25, CI = 0.16, 0.34, p < .001) with ADHD. The specificity of each temperament construct for later ADHD symptom dimensions was such that activity level and negative emotionality were predictive of all three symptom dimensions (i.e., inattention, hyperactivity/impulsivity, and combined), whereas sustained attention was only associated with combined symptoms. Conclusions: Infant and toddler temperament is an early risk factor for the development of childhood ADHD that could be utilized for early intervention identification. Yet, this systematic review found that relatively few prospective longitudinal studies have examined sustained attention ( k = 9) and inhibition ( k = 15) in infancy and toddlerhood in relation to later ADHD highlighting the need for further research.